(untitled) (TAJ: Journal of Teachers Association, 2010)
A 15 years young fair girl presented with primary amenorrhoea. Findings on her physical examination included short stature, cubitus valgus, slightly webbed neck, absent of secondary sexual characters, broad chest with widely spaced nipples and absence of pubic & axillary hair. Except for the above, her systemic examination was unremarkable. A gynecological examination failed to reveal any abnormality. Ultrasound examination of abdomen revealed absent uterus and ovaries. Serum T3, T4 were within normal level, but TSH level was in slightly raised. Plasma FSH & LH were high with low estradiol level suggestive of hypergonadotrophic hypogonadism. Karyotyping confirmed the diagnosis of Turner ’s syndrome (45, X0). TAJ 2010; 23(1): 91-94